2019
DOI: 10.1038/s41598-019-47251-z
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal structural disease progression of retinitis pigmentosa according to mode of inheritance

Abstract: We analyze disease progression in retinitis pigmentosa (RP) according to mode of inheritance by quantifying the progressive decrease of the ellipsoid zone (EZ) line width on spectral domain optical coherence tomography (SD-OCT) and of the dimensions of the hyperautofluorescent ring on short-wave fundus autofluorescence (SW-FAF). In this retrospective study of 96 patients, average follow-up time was 3.2 ± 1.9 years. EZ line width declined at a rate of −123 ± 8 µm per year, while the horizontal diameter and ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…With respect to disease progression, our nonlinear mixed models revealed that the IS/OS band width decreased linearly at a rate of − 112.4 μm (6.5%) per year; a similar rate was reported in a previous study of RP associated with variants of genes in the PDE6 gene family, including PDE6A and PDE6B (− 91 μm [5.9%]/year) 27 . However, the rate observed in this study is higher than that reported in other studies considering all types of RP (reported values vary from − 76.43 μm (4.16%)/year 28 to − 130 μm (4.9%)/year) 29 and studies considering autosomal dominant RP (3.8%/year), while it is lower than that reported for X-linked RP (9.4% μm/year) 30 . The generation of sophisticated predictions based on clinical information is a strength of this study.…”
Section: Discussioncontrasting
confidence: 84%
“…With respect to disease progression, our nonlinear mixed models revealed that the IS/OS band width decreased linearly at a rate of − 112.4 μm (6.5%) per year; a similar rate was reported in a previous study of RP associated with variants of genes in the PDE6 gene family, including PDE6A and PDE6B (− 91 μm [5.9%]/year) 27 . However, the rate observed in this study is higher than that reported in other studies considering all types of RP (reported values vary from − 76.43 μm (4.16%)/year 28 to − 130 μm (4.9%)/year) 29 and studies considering autosomal dominant RP (3.8%/year), while it is lower than that reported for X-linked RP (9.4% μm/year) 30 . The generation of sophisticated predictions based on clinical information is a strength of this study.…”
Section: Discussioncontrasting
confidence: 84%
“…The presentation of patients with asymmetric RP was also similar to patients with symmetric RP in regards to age of disease onset and severity of disease. It has been widely reported that XLRP is more severe than adRP 31 . This was also observed in our patient cohort, regardless of whether the patient presented with asymmetric disease or not.…”
Section: Discussionmentioning
confidence: 99%
“…Movement of TZ over time is likely driven by non-autonomous cell death mechanisms acting within or across photoreceptor types [75][76][77][78][79][80][81][82][83][84] . Importantly, definition of the TZ varies across investigations and can include some aspect of visual function 11,52,[85][86][87] , RPE atrophy or demelanization 13,73,[88][89][90] , extent of normal ONL thickness 71,87,91 , or the extent of the IS/OS signal detectability on OCT which demarcates severe OS abnormality 12,13,89,[92][93][94][95] . In a previous investigation, we showed that spatial progression of TZ as defined by the detectability of the IS/OS signal was greatest in the superior retina over a 2-year interval in Class B RHO-adRP 13 .…”
Section: Natural History Of Rod Photoreceptor Dysfunction In Human Irdsmentioning
confidence: 99%